DETECTION OF A SEISMIC SIGNAL BY A THREE-COMPONENT SEISMIC STATION AND DETERMINATION OF THE SEISMIC EVENT CENTER - Vakaliuk, T. A.; Pilkevych, I. A.; Hordiienko, Y. O.; Loboda, V. V.; Saliy, A. O. (Radio Electronics, Computer Science, Control, 2024)
Context. The work is devoted on the development of theoretical foundations aimed at automating process of determining location at the seismic event center. Objective. The purpose of the work is to develop a method for determining the center of a seismic event based on the use of the features of the angular characteristics of the constituent volume waves of a seismic signal obtained with the help of a threecomponent seismic station. The proposed method will reduce the time it takes to provide users with preliminary information about the fact of a seismic event and its parameters. Method. The method of automatic detection focal point is based on features of orthogonality in the angular characteristics volume waves registered sample of three-component seismic recordings from a certain direction. Implementation of the proposed approaches makes it possible to reduce the processing time of the seismic record with appropriate reliability compared to processing in manual mode.An example application of the proposed method (algorithm) for processing a seismic signal in the Vrancea zone on 27.10.2004 with magnitude M=5.7 is considered. Results. The proposed approach to processing the measured data of a separate seismic three-component seismic station using a polarization analysis device allows detecting the arrival of a seismic signal, identifying the main components of a seismic signal, and estimating the location of the epicenter of a seismic event.Experimental research on the use of the proposed algorithm for determining the location of the epicenter of a seismic event showed that the time of establishing an emergency event within the borders of Ukraine was reduced five times (from 15 to 3 minutes), and the detection error was 37 km. Conclusions. The formed basis and proposed approach to detecting a seismic signal, identifying its components and determining a seismic event focal point based on results of processing a three-component seismic record are effective. Proposed method (algorithm) should be used to automate process of seismic signal detection by a three-component seismic station and to determine the seismic event center.